2006
DOI: 10.1002/bit.21246
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption, absorption, and biological degradation of ammonia in different biofilter organic media

Abstract: A tailor-made apparatus called ammoniometer, which is a batch mode respirometer applied to the study of ammonia biodegradation in biofilter media, has been used to evaluate adsorption, absorption, and biodegradation in five different organic materials (compost, coconut fibre, bark, pruning wastes, and peat) obtained from full-scale biofilters in operation in several waste treatment plants. The results showed that absorption could be represented by a Henry's law linear equation, with values of the Henry coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
6

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 36 publications
(43 reference statements)
0
27
0
6
Order By: Relevance
“…No data have been found on ammonia removal efficiencies during the start-up of an industrial biofilter. Nevertheless, according to Pagans et al,6,26 no start-up phase in a laboratory scale biofilter was observed for the removal of ammonia due to the high ammonia adsorption and absorption capacity of the biofilter materials used. After this initial period, probably due to the fact that equilibrium absorption and adsorption capacities were reached, 26 a decrease in ammonia removal efficiency was observed.…”
Section: Biofiltration Of Exhaust Gases From the Composting Tunnels Vmentioning
confidence: 94%
“…No data have been found on ammonia removal efficiencies during the start-up of an industrial biofilter. Nevertheless, according to Pagans et al,6,26 no start-up phase in a laboratory scale biofilter was observed for the removal of ammonia due to the high ammonia adsorption and absorption capacity of the biofilter materials used. After this initial period, probably due to the fact that equilibrium absorption and adsorption capacities were reached, 26 a decrease in ammonia removal efficiency was observed.…”
Section: Biofiltration Of Exhaust Gases From the Composting Tunnels Vmentioning
confidence: 94%
“…Inlet toluene concentrations to evaluate the quantity adsorbed in materials were selected according to common VOC's concentration treated by biofiltration (between 100 and 1000 ppm) [7]. Studied support materials were previously sterilized using sodium azide (Sharlau) in a 10% (w/w) ratio to remove the interferences of biological activity during the adsorption measurements [17].…”
Section: Methodsmentioning
confidence: 99%
“…43 At the RH encountered during this measurement campaign (usually Ͻ75%), the particles have not undergone significant deliquescence, 43 which is consistent with the limited conversion of NH 3 to the condensed phase. 32 The dominance of organic material in particles at Feedlot C is an unusual scenario. According to nationwide Interagency Monitoring of Protected Visual Environments (IMPROVE) network measurements, particle composition in rural areas is typically dominated by ammonium sulfate and ammonium nitrate, although areas closer to urban centers contain increased levels of organic materials.…”
Section: Field Measurementsmentioning
confidence: 99%
“…The presence of such an extensive amount of organics provides additional surfaces for NH 3 adsorption and absorption under the right conditions. 31,32 The adsorption and absorption of NH 3 on organic surfaces is maximized at a moisture level of 50 -70% in the substrate. 33 Rigorous coincident measurements at the source and downwind but close to the source are required to assess the direct contribution and time scales of NH 3 to PM formation near the source.…”
Section: Introductionmentioning
confidence: 99%